IoT-Chain: Security of things for Pervasive, Sustainable and Efficient Computing using Blockchain - Majid Akhtar, Mohd; Raza Rizvi, Danish (EAI Endorsed Transactions on Energy Web, 2020)
This paper unfolds the infancy of the exquisite experience of the ‘Internet of Things’. It will address the thrilling potential of the looming opportunity of IoT & will echo the integration of things when harnessed with the bubble of internet. The topic is vulnerable due to handful factors but chiefly improves the insights and will observe exponential rise in the ‘Next generation’. The new rule enchanted for future will be “Anything that can be connected will be connected”. Moreover, cognitive consciousness of people will understand that IoT is the next big thing without procrastinating, in particular. This paradigm will review the implementation and challenges of several domotics technologies and others in general within the communication field and its contribution to the ‘Smart World’, exploring supplementary in fields of healthcare, living culture, transportation and furthermore that collectively rise for the world of Ubiquitous computing or Pervasive computing around us. Pervasive computing in short serves as a meaning where smart devices are connected as network and available all time. By scratching past, we have seen DDoS attack happening in 2016 via botnet attacks & malware from the devices such as IP security cameras, routers, printers. IoT as of now, have taken steps for the security but still lacks for the major part. Blockchain, the revolutionary technology behind the famous Bitcoin, which is cryptographically secured and decentralized, hence, can act as the liberator for the security of IoT devices. Blockchain in short are distributed immutable ledger that maintains the integrity of the network by achieving consensus algorithms like Proof of Work or Proof of Stake. Hence, an attacker won’t be able to take down the IoT devices as easy as it was taken down before and eventually, harder to attack or hack the network. This manuscript discusses the use of Blockchain technology implementation for the security of IoT devices along with the sustainable and energy efficient solution towards the problem stated and addresses the limitations, if any. We also discuss the future prospect for IoT, blockchain and other possible architectures.
Keywords: Internet of Things; Blockchain; Security; Pervasive Computing; Sustainable and Energy Eﬃcient Computing; Cryptography; Decentralization